Deontic scope restrictions beyond polarity - Yanovich, Igor (Proceedings of the Amsterdam Colloquium, 2013)
Deontic modals often have restricted scope with respect to clausemate negation. Recently attempts have been made to attribute all such restrictions to the polarity status of the respective modals ([Iatridou and Zeijlstra, 2013], [Homer, 2013]). I argue that once we examine the full range of cross-linguistic data, such a purely-syntactic account is hardly tenable. I suggest to complement polarity restrictions on deontics with semantic filters on scope. Conventions regarding such filters arise as speakers generalize from the range of actual uses that a pre deontic construction used to have.